Comparison of objectively measured and estimated cardiorespiratory fitness to predict all-cause and cardiovascular disease mortality in adults: A systematic review and meta-analysis of 42 studies representing 35 cohorts and 3.8 million observations - Ben Singh; Cristina Cadenas-Sanchez; Bruno G.G. da Costa; José Castro-Piñero; Jean-Philippe Chaput; Magdalena Cuenca-García; Carol Maher; Nuria Marín-Jiménez; Ryan McGrath; Pablo Molina-García; Jonathan Myers; Bethany Gower; et al. (Journal of Sport and Health Science)
Background: Cardiorespiratory fitness (CRF) is a powerful health marker recommended by the American Heart Association as a clinical vital sign. Comparing the predictive validity of objectively measured CRF (the “gold standard”) and estimated CRF is clinically relevant because estimated CRF is more feasible. Our objective was to meta-analyze cohort studies to compare the associations of objectively measured, exercise-estimated, and non-exercise-estimated CRF with all-cause and cardiovascular disease (CVD) mortality in adults. Methods: Systematic searches were conducted in 9 databases (MEDLINE, SPORTDiscus, Embase, Scopus, PsycINFO, Web of Science, PubMed, CINAHL, and the Cochrane Library) up to April 11, 2024. We included full-text refereed cohort studies published in English that quantified the association (using risk estimates with 95% confidence intervals (95%CIs)) of objectively measured, exercise-estimated, and non-exercise-estimated CRF with all-cause and CVD mortality in adults. CRF was expressed as metabolic equivalents (METs) of task. Pooled relative risks (RR) for all-cause and CVD mortality per 1-MET (3.5 mL/kg/min) higher level of CRF were quantified using random-effects models. Results: Forty-two studies representing 35 cohorts and 3,813,484 observations (81% male) (362,771 all-cause and 56,471 CVD deaths) were included. The pooled RRs for all-cause and CVD mortality per higher MET were 0.86 (95%CI: 0.83–0.88) and 0.84 (95%CI: 0.80–0.87), respectively. For both all-cause and CVD mortality, there were no statistically significant differences in RR per higher MET between objectively measured (RR range: 0.86–0.90) and maximal exercise-estimated (RR range: 0.85–0.86), submaximal exercise-estimated (RR range: 0.91–0.94), and non-exercise-estimated CRF (RR range: 0.81–0.85). Conclusion: Objectively measured and estimated CRF showed similar dose–response associations for all-cause and CVD mortality in adults. Estimated CRF could provide a practical and robust alternative to objectively measured CRF for assessing mortality risk across diverse populations. Our findings underscore the health-related benefits of higher CRF and advocate for its integration into clinical practice to enhance risk stratification.